The price responsiveness of shale producers: Evidence from micro data - Knut Are Aastveit; Hilde Christiane Bjørnland; Thomas Størdal Gundersen (Norges Bank, 2022)
We show that shale oil producers respond positively to favourable oil price signals, and that this response is mainly associated with the timing of production decisions through well completion and refracturing, consistent with the Hotelling theory of optimal extraction. This finding is established using a novel proprietary data set consisting of more than 200,000 shale wells across ten U.S. states spanning almost two decades. We document large heterogeneity in the estimated responses across the various shale wells, suggesting that aggregation bias is an important issue for this kind of analysis. Our empirical results call for new models that can account for a growing share of shale oil in the U.S., the inherent flexibility of shale extraction technology in production and the role of shale oil in transmitting oil price shocks to the global economy.
hdl:11250/3031787
Keywords: C23; Q41; Q43; 330